Paciente de sexo masculino de 57 años de edad, con diagnóstico de infarto cerebral, hipertensión arterial y diabetes mellitus tipo 2. - Moyano Salvador, Génesis Dayana (2021)
The following clinical case deals with a 57 year old male patient who is diagnosed with cerebral infarction, arterial hypertension and type II diabetes mellitus, this topic was chosen since today the study of chronic non-communicable diseases is vital importance worldwide because they are diseases that affect most of the population. The objectives of this case are to intervene nutritionally to the patient by carrying out a complete nutritional assessment in which it consists of interpreting anthropometric, biochemical, clinical and dietary data, making a personalized eating plan according to their nutritional needs, giving follow-up and monitoring through daily visits and be able to contribute to improving the nutritional status of the patient and thus be able to delay the complications of the disease. The patient was given a timely personalized nutritional intervention, in which a healthy eating plan was developed according to their nutritional needs, in this way it is possible to control the progression of the disease through the correct follow-up and monitoring that was carried out. Finally, it was possible to intervene the patient nutritionally with a correct nutritional evaluation and it was possible to contribute to improving the quality of life of the patient.